Efficacy of the Combination of Teriparatide and Denosumab in the Treatment of Postmenopausal Osteoporosis: A Meta-Analysis - Sun, Yang; Li, Yue; Li, Jiangbi; Xie, Xiaoping; Gu, Feng; Sui, Zhenjiang; Zhang, Ke; Yu, Tiecheng (Frontiers in Pharmacology, 2022)
Aims Evidence on the efficacy of combination treatment for patients with postmenopausal osteoporosis remains controversial. We aim to compare the efficacy between the combination treatment (teriparatide and denosumab) and other treatments among patients with postmenopausal osteoporosis. Methods and results We systematically searched PubMed, EMBASE, the Cochrane Library, and Web of Science up to January 26, 2022, for relevant studies. This meta-analysis reviewed all randomized controlled trials (RCTs) that reported on the combination treatment of teriparatide and denosumab in patients with postmenopausal osteoporosis. The articles were examined individually by two reviewers, and the relevant data was extracted. We combined weighted mean difference (WMD) for bone mineral density (BMD) using random- or fixed- effect models and conducted subgroup analyses. Sensitivity analyses were performed, and possible publication bias was also assessed. Overall, combination treatment enhanced the mean percent change of BMD in lumbar spine than other treatments (WMD=2.91, 95%CI: 1.983.83; P=0.00). And, combination treatment has been beneficial for enhancing the mean percent change of BMD in hip (WMD=3.19, 95%CI: 2.25~4.13; P=0.00). There was no significant difference between combination treatment and other treatments in terms of the adverse events (RR=0.82, 95%CI: 0.46~1.45; P=0.493). Conclusion This meta-analysis suggests that combination treatment of teriparatide and denosumab was superior to other treatments in terms of BMD enhancement at the lumbar spine and hip, without a raised risk of adverse events. The outcomes of the meta-analysis might provide a new treatment option for patients suffering from postmenopausal osteoporosis.